PENGARUH INSENTIF TERHADAP MOTIVASI KERJA DAN KINERJA PEGAWAI STIE ADI UNGGUL BHIRAWA SURAKARTA - Edhi Wasisto (ADVANCE, 2014)
The purpose of this study are to examine the effect of incentives on motivation and performance of employees at STIE AUB Surakarta. This study is a survey research. The data used is primary data collected through questionnaires to 33 employees at AUB STIE Surakarta. Data obtained are tested with test validity, reliability test, path analysis, t test, F test and R2 test. T test results showed that incentives have a significant effect on employees motivation, incentives have significantly influenceemployees performance and motivation. F test results show that the incentives and motivation variables affect the performance of employees at STIE AUB Surakarta simultaneously. The test results of path analysis show that the effect of incentive to employees performance through motivation is lower than the direct effect on employees performance of incentive variables. The test results show that the results of the total R2 is 78.6% and the remaining 21.4% described by other variables outside the model. Keywords : Incentives, motivation, employee performance.